PICTURE WORD INDUCTIVE MODEL FOR BETTER DESCRIPTIVE TEXT WRITING - Mira Ermita; Emzir Emzir; Ninuk Lustyantie (Indonesian EFL Journal, 2019)
This study is done to find out the effect of using the Picture Word Inductive Model for teaching-learning descriptive text with second-semester students in the English Education Study Program at the University of Jambi in Indonesia to improve the students’ writing skills. This study used an action research method. Three cycles were done in this study. Data were gathered from observations and tests. In the preliminary study, the mean score of the student’s speaking was 50. The percentage of students who passed the minimum criterion of 70 was 6% with only 1 out of 17 students passing the minimum score. The mean score from cycle 1 was 72 and only 11 students or 65% passed the minimum score. The mean score from cycle 2 was 67 and 41%, i.e. only 7 students passed the minimum score. Meanwhile, from cycle 3, the mean score was 80 and all of the students (100%) passed the minimum score. Hence, the results showed that the use of Picture Word Inductive Model was a success. The students enjoyed their lessons more and were more motivated, interested and confident during the teaching-learning sessions.